INDIVIDUAL DIFFERENCES IN STUDENTS IN THE ELEMENTARY SCHOOL ENVIRONMENT - Wahyuni, Hasanah Dwi; Nura, Shinta Anjani; Magdalena, Ina (PROGRES PENDIDIKAN, 2021)
Every human being was created by the Creator with all the uniqueness and characteristics of each. This arises as individual differences (individual differences). Individual differences are differences in abilities and characteristics (cognitive, personality, physical skills, and so on) between students at a certain age level and in each particular group. Through educational practices and activities, we can accommodate the individual differences of students. Likewise, the learning styles of each other are also different. There are visual, auditory, and kinesthetic learning styles. It is important to recognize the learning styles of students so that teachers can vary their teaching styles, learning methods that are suitable to be applied in the learning process. As a technique, we must be able to choose various ways that can accommodate these differences personally and optimize the improvement and interpersonal skills of each student in the long term, especially when viewed from the learning style so that it can be carried out optimally. Individual differences that need to be considered in the implementation of classroom teaching are factors related to the readiness of children to receive teaching because these differences will determine the education system as a whole. Factors that influence individual differences are self-concept (self-concept), locus of control, student anxiety, learning motivation.